Pregunta
upstudy study bank question image url

\[ P(x)=x^{3}+2 x^{2}-6 x-4, \quad c=2 \] Evaluate \( D(x) \) for the given value of c, (Simplify your answers completely,) \[ \begin{aligned} P(2) & =(2)^{3}+2(\square)-6(2)-4 \\ & =8+2(\square)-6(2)-4 \\ & =8+(\square)=12-4 \\ & =\square \square \square) \end{aligned} \] Since? \( \square \) is 3 zero of \( P(x), x=2 \) \( \square \) is a factor of \( P(x) \),

Ask by Rodriguez Warren. in the United States
Feb 27,2025

Solución de inteligencia artificial de Upstudy

Respuesta verificada por el tutor

Responder

\( P(2) = 0 \) and \( D(x) = x² + 4x + 2 \).

Solución

We are given   P(x) = x³ + 2x² – 6x – 4      and  c = 2. Step 1. Evaluate P(2):   P(2) = (2)³ + 2(2)² – 6(2) – 4      = 8 + 2(4) – 12 – 4      = 8 + 8 – 12 – 4      = 0 Thus, P(2) = 0. Step 2. Since P(2)=0, by the Factor Theorem, x = 2 is a zero of P(x) and (x – 2) is a factor. Step 3. To find D(x) (also called the depressed polynomial), perform synthetic division of P(x) by x – 2. Set up synthetic division using the coefficients of P(x):   Coefficients: 1  2  –6  –4   c = 2     Bring down the 1.     Multiply 1 by 2 -> 2. Add to 2 -> 4.     Multiply 4 by 2 -> 8. Add to –6 -> 2.     Multiply 2 by 2 -> 4. Add to –4 -> 0. The synthetic division steps:     2 |  1   2  –6  –4         2   4   2      –––––––––––––––       1   4   2   0 The quotient (depressed polynomial) is given by the coefficients 1, 4, and 2, which corresponds to:   D(x) = x² + 4x + 2 Summary of Fill-in-the-Blanks:   P(2) = (2)³ + 2(2)² – 6(2) – 4       = 8 + 2(4) – 6(2) – 4       = 8 + 8 – 12 – 4       = 0 Thus, since 0 was obtained, x = 2 is a zero of P(x) and hence (x – 2) is a factor. Final Answers:   P(2) = 0,   D(x) = x² + 4x + 2.

Respondido por UpStudy AI y revisado por un tutor profesional

error msg
Explicar
Simplifique esta solución

Extra Insights

First, let's evaluate \( P(2) \). Substituting \( c = 2 \) into your polynomial, we get: \[ P(2) = (2)^3 + 2(2)^2 - 6(2) - 4 = 8 + 8 - 12 - 4 = 0. \] This means that \( P(2) = 0 \)! Thus, \( (x - 2) \) is indeed a factor of \( P(x) \). Now, depending on how you like to express \( P(x) \), you can perform polynomial long division or synthetic division to factor \( P(x) \) as follows: Since \( P(x) = (x - 2)(\text{Quadratic}) \), you can find the other factor by dividing \( P(x) \) by \( (x - 2) \). When you do this, you'll find that \( P(x) \) can be factored into \( P(x) = (x - 2)(x^2 + 4x + 2) \). Let's get solving!

¡Prueba Premium ahora!
¡Prueba Premium y hazle a Thoth AI preguntas de matemáticas ilimitadas ahora!
Quizas mas tarde Hazte Premium
Estudiar puede ser una verdadera lucha
¿Por qué no estudiarlo en UpStudy?
Seleccione su plan a continuación
Prima

Puedes disfrutar

Empieza ahora
  • Explicaciones paso a paso
  • Tutores expertos en vivo 24/7
  • Número ilimitado de preguntas
  • Sin interrupciones
  • Acceso completo a Respuesta y Solución
  • Acceso completo al chat de PDF, al chat de UpStudy y al chat de navegación
Básico

Totalmente gratis pero limitado

  • Solución limitada
Bienvenido a ¡Estudia ahora!
Inicie sesión para continuar con el recorrido de Thoth AI Chat
Continuar con correo electrónico
O continuar con
Al hacer clic en "Iniciar sesión", acepta nuestros términos y condiciones. Términos de Uso & Política de privacidad